Análise da remodelação óssea peri-cervical em implantes unitários na região estética - Cosenza, Heitor Bernardes (2011)
The aim of the study was to evaluate pericervical remodeling comparing machined surface implants (Nobel Biocare Sweeden) to TiUnite® surface implants (Nobel Biocare Sweeden) on aesthetic site. For this purpose, ten machined implant patients and ten TiUnite® implant patients, with between four and six years of function, were selected. Radiographs were scanned and the thread pitch, known measure provided by Nobel Biocare of Brazil, was used to calibrate ImageJ software, digital image measuring tool. Consequently, radiograph distortion was minimized. Three points were set: angle between implant mirror and long axis wall, first point of bone/implant contact, remnant bone crest, respectively, A, B and C. They were all single implants and had neiboring teeth, mesial and distal. Distances were taken by one examiner three times between each relation (AB, AC, BC). Dahlberg formula was used to verify the method error and the results were evaluated by Student t test. There were no statistically significant difference between two groups. Consequently, it was possible to put the groups together, what resulted in 1,87mm in average of bone pericervical remodelin, from the implant mirror to the first implant/bone contact, in a period between four and six years.